Expression of Phosphofructokinase Is Not Sufficient to Enable Embden-Meyerhof-Parnas Glycolysis in Zymomonas mobilis ZM4 - Felczak, Magdalena M.; Jacobson, Tyler B.; Ong, Wai Kit; Amador-Noguez, Daniel; TerAvest, Michaela A. (Frontiers in Microbiology, 2019)
Zymomonas mobilis is a bacterium that produces ethanol from glucose at up to 97% of theoretical efficiency on a carbon basis. One factor contributing to the high efficiency of ethanol production is that Z. mobilis has a low biomass yield. The low biomass yield may be caused partly by the low ATP yield of the Entner-Doudoroff glycolytic pathway used by Z. mobilis, which produces only one ATP per glucose consumed. To test the hypothesis that ATP yield limits biomass yield in Z. mobilis, we attempted to introduce the Embden-Meyerhof-Parnas (EMP) glycolytic pathway (with double the ATP yield) by expressing phosphofructokinase (Pfk I) from Escherichia coli. Expression of Pfk I caused growth inhibition and resulted in accumulation of mutations in the pfkA gene. Co-expression of additional EMP enzymes, fructose bisphosphate aldolase (Fba) and triose phosphate isomerase (Tpi), with Pfk I did not enable EMP flux, and resulted in production of glycerol as a side product. Further analysis indicated that heterologous reactions may have operated in the reverse direction because of native metabolite concentrations. This study reveals how the metabolomic context of a chassis organism influences the range of pathways that can be added by heterologous expression.